(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This comprehensive exploration delves into the pivotal role of digital educational technologies in the realm of teaching foreign languages. Unveiling a transformative landscape, the article navigates through the multifaceted impacts of technology on language acquisition, from personalized learning journeys and accessible language resources to real-time collaboration and the cultivation of digital literacy skills. The narrative unfolds as a nuanced exploration of how digital tools enhance engagement, foster accessibility, and propel language education into a dynamic era of continuous evolution and innovation.